Model Pelayanan Promosi Kesehatan Jiwa Berbasis Maasyarakat: Literatur Riviwe - Lina Eta Safitri; Nurbaiti Zulkaidah; Surti Hatiya; Sulis Susilawati; Eldo Tawa Gara Meha; Alexander Umbu Neka Pajaga (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Mental health is a health problem that cannot be separated from other health problems, and is one of the problems that will become a burden for the state and families due to premature death and disability. Health services are services provided to students related to health, both preventive (prevention of disease), promotive (improving health), curative (treatment of disease) and reabilitative (recovery). Health Promotion is an effort to improve community capabilities through learning from, by, for and with the community, so that they can help themselves, as well as developing activities that are community resourced, appropriate to local social culture and supported by health-oriented public policies. This study uses all articles presented in the form of a literature review regarding